Contemporary burden of excess cardiovascular mortality on Monday. A retrospective study in the Veneto region of Italy. (1st July 2016) - Capodaglio, Giulia; Gallerani, Massimo; Fedeli, Ugo; Manfredini, Roberto
Abstract: Background: An increased risk for adverse cardiovascular events on Monday has been consistently reported in the literature. It remains to be assessed if a Monday peak in cardiovascular deaths can still be detected within the contemporary context of decreasing mortality rates from circulatory diseases in developed countries. Methods: Mortality records were extracted from January 2000 to December 2013 in the Veneto region (Italy). The Monday excess in mortality from cerebrovascular diseases, ischemic heart diseases, and other circulatory diseases was investigated in subjects aged 35–74 years by means of Poisson regression models adjusted by age, gender, time trend and seasonality. Results: Among 41, 024 deaths from circulatory diseases registered in the study population, mortality rates on Monday were increased by 13% (CI 9–17%) with respect to Sunday and by 6% (CI 4–9%) with respect to the overall daily mean. The Monday peak could be detected in both genders and in all the analyzed disease categories, and was more pronounced in younger age classes and in more recent years. Conclusions: The persistency of the Monday effect on cardiovascular mortality is confirmed by recent large population-based data. Further research is warranted to investigate causal mechanisms.